Some New Exact Wave Solutions For The ZK-BBM Equation - Jianxi Yu (Journal of Applied Science and Engineering, 2022)
The generalized algebra technique is used to search for exact wave solutions of the ZK-BBM equation in this article. This equation is a notable model for describing the acoustic waves in harmonic crystals, shallow water waves etc. By applying the wave transformation, we obtained an ordinary differential equation. We have successfully obtained many exact wave solutions with arbitrary parameters by the method that exact wave solutions are expressed in terms of generalized hyperbolic function solution, generalized trigonometric function solution, exponential function solution, and rational function solution. The results show that the generalized algebra technique is a very concise and powerful mathematical tool for nonlinear evolution equations in engineering and science.